Legal Protection for Patients in Therapeutic Agreements According to Islamic Law - Sheila Megarani; Irwansyah Irwansyah; Elsa Yoreina Purba; Fadhlan Al Hafizh Marpaung (PROMOTOR, 2024)
A therapeutic agreement is an agreement formed as a result of an agreement between a doctor and a patient. This research examines the legal aspects of therapeutic agreements between doctors and patients in health services. This research aims to provide a legal protection mechanism for patients as one of the parties in a therapeutic agreement between a patient and a doctor. This research is useful for providing legal stability and patient protection in therapeutic agreements between patients and doctors. Apart from that, it can also be used as an effort for patients and doctors to understand their rights and obligations. The nature of the agreement between the doctor and the patient in providing patient services is that the aim of the agreement is an effort or therapy to cure the patient; Doctor-patient agreements have unique characteristics that differentiate them from other types of agreements; and an agreement between a doctor and a patient is not a resulting agreement because it does not concern the outcome of the medical services provided by the doctor or the conduct or treatment of those services. There are several principles of agreement in Islamic sharia law, including the principles of monotheism, permissibility, freedom of contract, justice, equality, honesty, trust, benefit and benefit, consensualism, binding promises, balance of performance, legal certainty, and personality.